Keteguhan Rekat Kayu Lapis Sengon Menggunakan Perekat Lignin-Formaldehida dengan Dua Macam Bahan Pengisi (Bonding Strength of Sengon Plywood Using Lignin-Formaldehyde Adhesive with Two Types of Fillers) - Achmad Supriadi; Adi Santoso; Rohmah Pari (Masyarakat Peneliti Kayu Indonesia, 2019)
Various efforts have been done to reduce the cost, such as finding a suitable mixture of fillers in the adhesive formulation. The aim of this study was to determine the characteristic of lignin-formaldehyde (LF) adhesive and the effect of different content of coconut shell flour and kaolin in the adhesive of lignin on the bonding strength of sengon plywood. Coconut shell flour and kaolin filler content were varied, i.e. 0%, 10%, 20%, 30%, and 40%. The plywood of (20x20x1.5) cm3 size was prepared using a liquid lignin-formaldehyde (LF) with a glue spread of 170 g m-2 surfaces. Bonding strength of plywood was tested to determine the quality of sengon plywood. The results showed that LF adhesive was appeared as a reddish-brown liquid and there were no foreign substances, solid resin content ranges from 31.85 to 35.68%, viscosity of 1.2 poise, acidity (pH) of 11.5, and gelatinized time ranges from 24.20-25.96 minutes. The type and filler content had a significant effect on the bonding strength of sengon plywood. Increasing of the filler content tended to increase the bonding strength of sengon plywood to 30%. The bonding strength of sengon plywood produced using the content of either coconut shell or kaolin flour fillers up to 30% complied with German Standards requirement. The maximum bonding strength value was obtained on adhesives using both types of fillers as much as 10 %.